2020
DOI: 10.3390/w13010015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Mesostructure Deformation Characteristics of Unsaturated Tailings with Different Moisture Content

Abstract: A portion of the accumulated tailings in a tailings pond exhibits an unsaturated state. The mechanical properties of unsaturated tailings affect the safety and stability of tailings dams. To investigate the effect of moisture content on the deformation characteristics of unsaturated tailings in the mesoscale, a special testing apparatus is applied to experimentally study the settlement deformation and mesostructure evolution of unsaturated tailings under continuous load. The results show that the mesostructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Figure 4 and Figure 5 show that with the increase in freeze–thaw cycles, there is a lack of regularity in the relationship between axial strain and UCS, which may be caused by the complexity and heterogenous influence of freeze–thaw cycles on the internal structure of loess specimens. The freeze–thaw cycle expands the specimen volume and loosens the particle structure, resulting in a complex stress transmission process and strain increase process under compression load [ 52 ].…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Figure 4 and Figure 5 show that with the increase in freeze–thaw cycles, there is a lack of regularity in the relationship between axial strain and UCS, which may be caused by the complexity and heterogenous influence of freeze–thaw cycles on the internal structure of loess specimens. The freeze–thaw cycle expands the specimen volume and loosens the particle structure, resulting in a complex stress transmission process and strain increase process under compression load [ 52 ].…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…After the liquefied tailings are fully consolidated again, the number of liquefaction failure cycles is significantly larger than the original one. This is due to the increased compaction of the tailings due to vibration and subsequent drainage consolidation (Geng et al, 2021). The liquefaction number of tailing silt increased from 67 to 1770 and that of tailing silt increased from 47 to 2065.…”
Section: Excess Pore Water Pressurementioning
confidence: 99%
“…Gregor Petkovšek et al [13] proposed a dam break model EMBREA-MUD to calculate the water and tailings outflow of the tailings reservoir and the corresponding break growth. Weile Geng et al [14] conducted experimental research on the settlement deformation and mesostructure evolution of unsaturated tailings under continuous load. The results showed that the mesostructure deformation of unsaturated tailings with different moisture contents under load was the same and could be divided into four stages: pore compression, elastic deformation, structure change, and further compaction.…”
Section: Introduction 1research Statusmentioning
confidence: 99%